2017
DOI: 10.1016/j.phrs.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemokines in hypertension and consequent target organ damage

Abstract: Immune cells infiltrate the kidney, vasculature, and central nervous system during hypertension, consequently amplifying tissue damage and/or blood pressure elevation. Mononuclear cell motility depends partly on chemokines, which are small cytokines that guide cells through an increasing concentration gradient via ligation of their receptors. Tissue expression of several chemokines is elevated in clinical and experimental hypertension. Likewise, immune cells have enhanced chemokine receptor expression during h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 91 publications
3
29
0
1
Order By: Relevance
“…33,34 Infiltrating leukocytes can also produce proinflammatory cytokines including TNF-α which further induce the expression of chemokines such as MCP-1 in resident tissue cells forming a positive feedback loop. 35 The current study provides some evidence of this with increased MCP-1 and adhesion molecule expression in the UN-S group which is associated with an increase in plasma TNF-α concentrations as well as renal mRNA expression. MCP-1 is associated with hypertensive conditions, and inhibiting its action reduces macrophage infiltration, normalizes blood pressure, prevented chronic renal damage and vascular inflammation in the hypertensive rat.…”
Section: Discussionsupporting
confidence: 53%
“…33,34 Infiltrating leukocytes can also produce proinflammatory cytokines including TNF-α which further induce the expression of chemokines such as MCP-1 in resident tissue cells forming a positive feedback loop. 35 The current study provides some evidence of this with increased MCP-1 and adhesion molecule expression in the UN-S group which is associated with an increase in plasma TNF-α concentrations as well as renal mRNA expression. MCP-1 is associated with hypertensive conditions, and inhibiting its action reduces macrophage infiltration, normalizes blood pressure, prevented chronic renal damage and vascular inflammation in the hypertensive rat.…”
Section: Discussionsupporting
confidence: 53%
“…A number of previous studies have shown that the course of hypertension is accompanied by local and systemic inflammation [17][18][19] . The previous studies have found that H-type hypertension patients are more prone to have cerebral infarction, suggesting that Hcy has a high probability of causing ischemic strokes 20 .…”
Section: Comparison Of Imts Before and After Treatment In Both Groupsmentioning
confidence: 99%
“…However, this finding is contrary to previous studies which have suggested that CCL5 plays an important protective role in hypertension-induced renal injury. In the angiotensin II-induced hypertension mice model, CCL5 gene deficiency exhibited markedly aggravation of kidney damage, macrophage infiltration, and proinflammatory cytokine expression, which led to the aggravation of urinary albumin excretion (Rudemiller and Crowley, 2017). This may be explained by the blockade of one chemokine leading to the upregulated expressions of other cytokines that exacerbate RASdependent hypertension, as CCL2 blockade abrogates the enhanced renal macrophage infiltration and interstitial fibrosis in CCL5deficient mice (Mikolajczyk et al, 2016;Rudemiller et al, 2016).…”
Section: Hypertensionmentioning
confidence: 97%